2023
DOI: 10.1093/cvr/cvad092
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive iron supplementation prevents myocardial iron deficiency and attenuates adverse remodelling after myocardial infarction

Abstract: Aims Heart failure (HF) after myocardial infarction (MI) is a major cause of morbidity and mortality. We sought to investigate the functional importance of cardiac iron status after MI and the potential of preemptive iron supplementation in preventing cardiac iron deficiency (ID) and attenuating left ventricular (LV) remodelling. Methods and results MI was induced in C57BL/6J male mice by left anterior descending coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Furthermore, it is important to differentiate ischemia and I/R injury as distinct pathological processes. A recent study provided evidence supporting the beneficial effects of iron supplementation after MI [52]. In our study, we found that SLC40A1 and Steap4 were upregulated in the ischemic areas during the initial phase of MI.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, it is important to differentiate ischemia and I/R injury as distinct pathological processes. A recent study provided evidence supporting the beneficial effects of iron supplementation after MI [52]. In our study, we found that SLC40A1 and Steap4 were upregulated in the ischemic areas during the initial phase of MI.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, the interaction between ROS, iron balance, and lipid peroxidation in the myocardium opens the way for new therapeutic targets in the management of ischemic heart diseases. For example, the investigation of molecules and pathways of ferroptosis, including ferroportin [ 71 ], FOXO1 [ 72 ], and others, may provide useful insights into the causal relationships between iron metabolism, ROS, and myocardial viability following ischemia.…”
Section: The Role Of Vitamin C In Cardiovascular Pathologiesmentioning
confidence: 99%
“…58,[111][112][113] Clinically, patients with iron deficiency have increased cardiac TfR1 expression and impaired cardiac energetics. 114,115 Yet, independently of systemic iron, failing hearts have decreased myocardial iron content and reduced mitochondrial activity, as well as decreased hepcidin, increased ferroportin and decreased sTfR 110,116,117 ; the latter findings suggests diminished entry into and enhanced egress of iron from cardiomyocytes. Furthermore, experimental chronic sympathetic stimulation causes intracellular iron deficiency and mitochondrial dysfunction in cardiomyocytes, 118 and increased plasma norepinephrine is associated with cardiac iron depletion, low sTfR and low TSAT in patients with heart failure.…”
Section: Search For Useful Diagnostic Criteria For Iron Deficiency In...mentioning
confidence: 99%
“…[121][122][123][124][125] Functional iron deficiency explains why patients with heart failure do not respond favourably to oral iron, whose slow pharmacokinetics allow for trapping in macrophages and hepatocytes. 126 With the progression of heart failure, serum levels of both hepcidin and ferritin may be affected by occult gastrointestinal bleeding, 125 by changes in hepatic function related to congestion inflammation, 82,83,127 by changes in intracellular expression of both proteins in response to stress or injury, 110,116,117 or by the use of certain foundational drugs for heart failure, which can reduce serum levels of both hepcidin and ferritin. 124,128 For all these reasons, neither serum ferritin nor hepcidin levels can be used to reliably identify iron-deficient patients with heart failure.…”
Section: Search For Useful Diagnostic Criteria For Iron Deficiency In...mentioning
confidence: 99%